2018
DOI: 10.1038/s41375-018-0135-8
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1/2 trial of GCLAM with dose-escalated mitoxantrone for newly diagnosed AML or other high-grade myeloid neoplasms

Abstract: Outcomes with “7+3” are often unsatisfactory in acute myeloid leukemia (AML). Trials demonstrating improved outcomes with high-dose cytarabine, addition of cladribine, or escalated anthracycline doses prompted a phase 1/2 study (NCT02044796) of G-CSF, cladribine, high-dose cytarabine, and dose-escalated mitoxantrone (GCLAM) in adults with newly-diagnosed AML or other high-grade myeloid neoplasms. 121 patients, median age 60 (range: 21–81) years, were enrolled. In phase 1, cohorts of 6–12 patients were assigned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 35 publications
(39 reference statements)
1
34
0
Order By: Relevance
“…• Fludarabine, high dose cytarabine, and idarubicin (FLAG-ida) has been shown to be an effective regimen 102 ○ Superior rates of remission and reduced risk of relapse compared with a 10 day cytarabine plus daunorubicin regimen were shown, but also with increased toxicity and thus no improvement in overall survival • Other intensive cytotoxic regimens incorporating clofarabine have been investigated [103][104][105] • Cladribine, another nucleoside analog, has also been investigated in combination with daunorubicin and cytarabine (eg, the "DAC regimen"), with response rates of up to 70% in de novo acute myeloid leukemia (AML) and 40-50% in relapsed/refractory AML 83 blasts to linger in an immature state. 8 The addition of the isocitrate dehydrogenase inhibitors blocks this process and allows for resumption of more normal differentiation, sometimes leading to the complication of "differentiation syndrome," in which the rapid maturation of many immature white blood cells leads to dyspnea, fever, pulmonary infiltrates, and hypoxia.…”
Section: Conventional Chemotherapymentioning
confidence: 99%
“…• Fludarabine, high dose cytarabine, and idarubicin (FLAG-ida) has been shown to be an effective regimen 102 ○ Superior rates of remission and reduced risk of relapse compared with a 10 day cytarabine plus daunorubicin regimen were shown, but also with increased toxicity and thus no improvement in overall survival • Other intensive cytotoxic regimens incorporating clofarabine have been investigated [103][104][105] • Cladribine, another nucleoside analog, has also been investigated in combination with daunorubicin and cytarabine (eg, the "DAC regimen"), with response rates of up to 70% in de novo acute myeloid leukemia (AML) and 40-50% in relapsed/refractory AML 83 blasts to linger in an immature state. 8 The addition of the isocitrate dehydrogenase inhibitors blocks this process and allows for resumption of more normal differentiation, sometimes leading to the complication of "differentiation syndrome," in which the rapid maturation of many immature white blood cells leads to dyspnea, fever, pulmonary infiltrates, and hypoxia.…”
Section: Conventional Chemotherapymentioning
confidence: 99%
“…• Intensive chemotherapy, often followed by hematopoietic cell transplantation, continues to be a standard of care for AML and offers the best chance for long-term remission • Newer intensive strategies for AML include novel chemotherapy designs and chemotherapy as a backbone in combination with targeted agents • Many older adults with AML benefit from receiving intensive chemotherapy with a curative intent, and a more holistic approach to determining eligibility for intensive treatment is recommended guidelines [5,7]; however, while these regimens have all demonstrated efficacy in AML, studies have not consistently supported the use of one regimen over another [24][25][26][27][28].…”
Section: Article Highlightsmentioning
confidence: 99%
“…Because randomized trials demonstrated dose-dependent anti-leukemic efficacy of anthracyclines during induction chemotherapy [3-5], we recently conducted a single-center phase 1/2 trial (ClinicalTrials.gov: NCT02044796) testing CLAG-M with escalated doses of mitoxantrone in separate cohorts of fit adults ≥18 years with either newly-diagnosed or relapsed/refractory AML and other high-grade myeloid neoplasms (≥10% myeloblasts in blood and/or marrow) [6, 7]. In both cohorts, medical fitness was defined by a treatment-related mortality (TRM) score of ≤6.9, a score that corresponds to a ≤6.9% probability of 4-week mortality [8].…”
mentioning
confidence: 99%
“…In the newly-diagnosed arm, we enrolled 121 patients with a median age of 60 (range: 21-81) years [6]. Because all 4 mitoxantrone doses were well-tolerated, 18 mg/m 2 was declared the RP2D in this arm.…”
mentioning
confidence: 99%